An analysis of guest attitude toward dining at green restaurants in Qatar - MC Ashim Sagar; Eddy Kurobuza Tukamushaba; Juliet Gladies Jayasuria; Khalid Ibrahim Al-Sulaiti (Research in Hospitality Management)
This study examines how interpersonal influence, green menu attributes and eco-friendly attributes shape guest attitudes toward green dining in five-star hotels in Qatar, and how these attitudes influence their willingness to dine at green restaurants. Using a quantitative approach, a structured survey was administered to 110 respondents. Findings reveal that green menu attributes and eco-friendly practices significantly influence attitudes toward green dining, while interpersonal influence has limited impact. These attitudes, in turn, strongly predict willingness to dine at green restaurants, reflecting global trends in sustainable dining. The study recommends that hospitality establishments leverage this growing market by incorporating green menus, adopting zero-waste practices, and targeting male customers to enhance revenue, promote sustainability, and encourage healthier lifestyles.